(untitled) (Research, Society and Development, 2021)
The high use of pesticides in agricultural plantations to combat pests and insects can cause many damage to people’s health. These practices are widely found in crops in the northern region of Mato Grosso. The aim of this study was to use Information and Communication Technologies (ICT) to sensitize students about the indiscriminate use of pesticides. This is a qualitative study. The group participating in the research was composed of five students from the São Vicente de Paula state school in the municipality of Sinop. For gathering information and constituting data, a Virtual Conversation Wheel (RCV) was developed as a teaching and learning methodology and the analysis of these questions can be classified as qualitative descriptive research. For the development of the research, four pedagogical moments were used: pre-questionnaire, virtual conversation wheel for the exhibition of ideas, explanation of the content made by the teacher, post-questionnaire. The data were collected by the teacher through the application of questionnaires and the RCV with aspects of concept evaluation and subjective aspects. Therefore, the use of RCV is a teaching and learning methodology that favors the reading of socioenvironmental issues, as students had a better argument on the subject, with more grounded concepts than initially with questions related to the use of pesticides, expanding the students’ knowledge and awareness of the implications of the indiscriminate use of these products in agricultural production.